Balantidium coli or Balantioides coli? Balantidiosis or Balantiosis? - Cazorla-Perfetti, Dalmiro (2018)
Mr. Editor We have read with special attention and interest the article by Condemayta et al (2018), where they present the results of an epidemiological study on the prevalence of infection by the intestinal parasite "Balantidium coli" and the risk factors associated with its transmission. in humans and pigs in two populations of the Acora District, province and Department of Puno, Peru. In general, we agree with the content of the article. However, we wish to comment on the taxonomic and systematic status of "Balantidium coli", and the corresponding nomenclature of the enteroparasitic disease it causes, which we consider require updating in light of the new evidence and findings presented in the scientific literature of the area, especially those of the molecular type. In this sense, it should first be indicated that the genus Balantidium belongs to the Phylum Ciliophora (Class Litostomatea, order Vestibuliferida, family Balantidiidae), and is made up of more than 80 species of eukaryotic-ciliated microorganisms that live in a parasitic way within the gastrointestinal tract of a wide variety of invertebrates and vertebrates. (Chistyakova et al., 2014). The genus Balantidium was created when Bursaria entozoon was separated from the genus Bursaria, and later assigned to Balantidium entozoon, which is the isolated type species of anurans (frogs) (Chistyakova et al. 2014). Many species of the genus Balantidium have been isolated and identified from amphibians, fish, and insects; by contrast, all isolates made in mammals were assigned to Balantidium coli, which was originally obtained from human patients with dysentery and assigned as Paramecium coli. However, the fact that the vast majority of these classifications have been based almost exclusively on morphological observations with photon microscopy, especially of trophozoites, has led to confusion, controversies and synonyms due to the wide variability they exhibit (Pomajbíková et al., 2013 ; Chistyakova et al., 2014). This problem has led researchers in the area to apply new tools and criteria such as phylogenetic-molecular ones to establish genetic affinity relationships between the wide variety of isolates of "B. coli", as well as with other Balantidium species. spp., from different hosts, which include, in addition to humans and pigs, among others, non-hominid primates, camels and birds (Pomajbíková et al. 2013, Chistyakova et al. 2014). The first results strongly indicate that Balantidium spp. is markedly polyphyletic, and is made up of three different groups or clades according to the specificity with their hosts, which include amphibian parasites (B. entozoon, B. duodeni, and Balantidium sp. F7 isolation), fish (B. polyvacuolum, B ctenopharyngodonis) and homeothermic vertebrates (B. coli). By highlighting the fact that the "B. coli" taxa were phylogenetically distant from the type species of the genus Balantidium (B. entozoon), then Pomajbíková et al. (2013) proposed the creation of a new genus Neobalantidium; however, this turned out to be a synonym for Balantioides, so according to the International Code of Zoological Nomenclature, this last genus should prevail. Therefore, the species must be named Balantioides coli (Chistyakova et al., 2014). In the light of this new taxonomic proposal, then the disease caused by B. coli should be called balantiosis and not balantidiosis (= balantidiasis). Regarding the location at the level of classification systems in eukaryotes, traditionally B. coli has been located within protozoa, as Condemayta et al (2018) did in their referred article. The advances that occur today at the level of phylogenetic studies have allowed new proposals to be made. Thus, in the Cavalier-Smith kingdom system, ciliates such as B. coli are located within the Chromista Kingdom and not in Protozoa (Cavalier-Smith, 2018). In this same sense, other authors have also applied the criteria of molecular phylogeny and have begun to form "groups" or "super groups" instead of kingdoms, placing B. coli and ciliates within the SAR super group (Estramenopila + Alveolados + Rizaria) or the Alveolata group (Baldauf, 2008; Burki et al., 2016). Taking into consideration all the aforementioned, then it is necessary to homogenize all this new nomenclature of both the etiological agent (Balantioides coli) and the respective enteroparasitic entity that causes (balantiosis), in the journals of our environment and particularly in the Journal of High Andean Research ( National University of the Altiplano of Puno, Peru).